Requirements for Business Process Re-engineering at Tishreen University (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This research investigates the requirements of an application business process reengineering at Tishreen University. This approach depends on the basic rethinking and redesign operations for achieving a direct improvement in the normal performance measurements. In order to achieve the goals of this study were used the researcher the descriptive approach. The study used a comprehensive inventory method for disruptive individuals as director and head of department in the central administration. And it used the questionnaire as a basic tool to collect data. The results have indicated that the questionnaire parameters were very reliable and the order of the administrative requirements available for the application of Business Process Reengineering as follows: a willingness to change 3.30, the strategy 3.12, the commitment of senior management 3.06, empowering employee 2.93. and the most important recommendations were: spreading and enhancing the concept of Business Process Reengineering within the employees.   متطلبات إعادة هندسة العمليات الإدارية في جامعة تشرين يتناول هذا البحث دراسة متطلبات تطبيق مدخل إعادة هندسة العمليات الإدارية في جامعة تشرين، ويقوم هذا المدخل على إعادة التفكير الأساسي، وإعادة التصميم الجذري للعمليات للتوصل إلى تحسينات فورية في مقاييس الأداء المعروفة. لتحقيق أهداف الدراسة استخدمت الباحثة المنهج الوصفي، واستخدمت الدراسة أسلوب الحصر الشامل على الأفراد الشاغلين وظيفة المدير ورئيس دائرة في الإدارة المركزية،(52). واستخدمت الدراسة الاستبانة كأداة رئيسة لجمع البيانات. وكان ترتيب المتطلبات الإدارية المتوافرة لتطبيق إعادة هندسة العمليات الإدارية وفقاً لما يلي: الاستعداد للتغيير(3.30)، الاستراتيجية(3.12)، التزام الإدارة العليا(3.06)، تمكين العاملين(2.93). أي أن الجامعة لا تمتلك الحد الأدنى من المتطلبات الإدارية. وكان من أهم التوصيات نشر وتعزيز مفهوم إعادة هندسة العمليات الإدارية بين الموظفين.